PERILAKU KOMUNIKASI WANITA SYIAH DALAM PERNIKAHAN MUT’AH - Nurlimah, Nila (EDUTECH, 2014)
Abstract. This research was also intended to find out the communication behavior of the actors of mut’ah marriage to either their husbands or their surrounding communities. This research used the qualitative method by using the symbolic interaction approach The dramaturgical attitude in front of Sunni communities and mature attitude in doing the mut’ah marriage were the consequence of the marriage The results of the research show that, communication behavior of Syiah women that could be seen from two aspects, namely: 1) In the Polygamy Mut’ah actors, mut’ah of Sunni husband, and continuous mut’ah with different husband, the verbal communication used tended to be very careful with limited non-verbal communication, and the mediated communication as wished. Meanwhile, in the monogamy mut’ah, mut’ah without intimate course, mut’ah with Syiah husband, and continuous mut’ah with the same husband the verbal communication was very expressive with common non-verbal communication, and unlimited mediated communication.2) In the aspect of interaction to the environment, all mut’ah actors had opened attitude to the Syiah and closed attitude to the Sunni.Key Word: communication behavior, mut’ah marriage, syi’ah womenAbstrak. Penelitian ini dimaksudkan untuk mengungkap perilaku komunikasi para pelaku nikah mut’ah baik dengan suami maupun dengan lingkungan sekitar.Penelitian dengan menggunaka pendekatan studi interaksi simbolik ini memperlihatkan adanya sikap dramaturgis di hadapan masyarakat Sunni dan sikap dewasa dalam menjalani pernikahan mut’ah, .Hasl penelitian menunjukkan bahwa pada pelaku mut’ah poligami, mut’ah suami Sunni, dan mut’ah berkali-kali dengan suami yang berbeda perilaku komunikasi verbal cenderung hati-hati, komuni kasi non verbal terbatas, dan komunikasi bermedia seperlunya. Sementara pada mut’ah monogami, mut’ah tanpa hubungan intim, mut’ah dengan suami Syi’ah, mut’ah berkali-kali dengan suami yang sama komunikasi verbal lebih ekspresif, komunikasi non verbal wajar, dan komunikasi bermedia leluasa. Pada aspek interaksi dengan lingkungan semua pelaku mut’ah bersikap sama terhadap lingkungan yaitu terbuka terhadap kalangan Syiah dan tertutup terhadap kalangan non Syiah.Kata Kunci : perilaku komunikasi, wanita Syiah, nikah mut’ah